Teachers’ Experiences of Facilitators and Barriers to Implement Theme-Based Cooperative Learning in a Swedish Context - Fohlin, Lisa; Sedem, Mina; Allodi, Mara Westling (Frontiers in Education, 2021)
Implementing Evidence-Based Practice (EBP) in school settings can be challenging. This case study presents barriers and facilitators expressed by kindergarten teachers (N=6) during the implementation of a theme-based cooperative learning project over the course of a semester. During three group interviews, at the start, mid-point, and end, the teachers expressed their thoughts and experiences about the project. The Theoretical Domains Framework (TDF) was used to identify and analyze barriers and facilitators throughout the project. The importance of organizational investment, collegial connection and collaboration, the pedagogical fit of the EBP, and plans for long-term change were highlighted as beneficial factors for successful implementation in this case study.